1.05t+0.63=-0.07t

Simple and best practice solution for 1.05t+0.63=-0.07t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.05t+0.63=-0.07t equation:


Simplifying
1.05t + 0.63 = -0.07t

Reorder the terms:
0.63 + 1.05t = -0.07t

Solving
0.63 + 1.05t = -0.07t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '0.07t' to each side of the equation.
0.63 + 1.05t + 0.07t = -0.07t + 0.07t

Combine like terms: 1.05t + 0.07t = 1.12t
0.63 + 1.12t = -0.07t + 0.07t

Combine like terms: -0.07t + 0.07t = 0.00
0.63 + 1.12t = 0.00

Add '-0.63' to each side of the equation.
0.63 + -0.63 + 1.12t = 0.00 + -0.63

Combine like terms: 0.63 + -0.63 = 0.00
0.00 + 1.12t = 0.00 + -0.63
1.12t = 0.00 + -0.63

Combine like terms: 0.00 + -0.63 = -0.63
1.12t = -0.63

Divide each side by '1.12'.
t = -0.5625

Simplifying
t = -0.5625

See similar equations:

| 4x+2(8)=4x(9) | | 10n+2=22 | | 13-6b=3+11b | | 9n+18=36 | | (99+x)=(176+y) | | -9(x+3)+3x+6=5x+9 | | 6.75t+7=15.5t+14 | | 4568b-4=7 | | -v+2=3 | | 116=-4(-4y)-9(2y)+y | | (w*3-9)+(w+4)=(w*3-9)+(w+4) | | 2x+3y=5.13 | | 16+b^2+6b=0 | | 4y^6(y^2+9y+2)= | | 8n^2-3n-16=24 | | -10+3x=-4 | | X+y=y+x+200 | | 57=3v+3 | | 89-116=-4(-4y)-9(2y) | | 4x+6+6x=36 | | x+y+z=2000zxy | | (7x-4x)=y | | -5x-2=-2x-17 | | 0.5(2n-10)=22 | | -4x+5+6x=37 | | 183=3+10x | | 20+x*-4=44 | | 12x-10=8x | | 15n=6+25 | | 15n=6+255 | | 7p-2r-6r-2p= | | 5-7m=5 |

Equations solver categories